THE CONTRIBUTIONS OF WOMEN ORGANIZATIONS IN COMMUNITY DEVELOPMENT IN NIGERIA - J. J., YIDAU; A. A, TAFIDA, .; I. D, YUSUF (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
This paper reviewed the roles/activates of the women organizations; identified the level of some women organizations contributions in the community and the constraints of these organizations participation. The review identified some leading women organizations and their contributions to the community development such as distribution of relief materials to IDPs, donations to victims of Nyanya bomb blasts. Distribution of materials inmates in prison, provision of community health centers , built schools and day care centers mention but a few. The constraints identified were inadequate funds; embezzlement of some scare resources; others were illiteracy; limited access to political network and disunity. It is therefore recommended that empowerment and education should be targeted towards women to raise role models.